Exposure to multiple disasters: The long-term effect of Hurricane Sandy (October 29, 2012) on NYC survivors of the September 11, 2001 World Trade Center attack. (March 2019) - Gargano, Lisa M.; Li, Jiehui; Millien, Lucie; Alper, Howard; Brackbill, Robert M.
Highlights: 9/11-related PTSD history effects the role Sandy experiences play on the risk of subsequent 9/11-related PTSD. Those who report lower optimism after Sandy were at greater risk for post-Sandy 9/11-related PTSD. Sandy-related PTSD was the strongest predictor of post-Sandy 9/11-related PTSD. Abstract: This study evaluated the impact of pre-Hurricane Sandy (Sandy) post-traumatic stress disorder (PTSD) trajectories on the relationship between Sandy exposures and post-Sandy 9/11-related PTSD among World Trade Center Health Registry (Registry) enrollees. The study population included 3, 199 adult Registry enrollees who completed three surveys prior to Sandy in 2003–4, 2006–7, and 2011–12; a post-Hurricane Sandy survey (2013); and a follow-up survey in 2015–16. PTSD was assessed using the PTSD Checklist (PCL). Latent class growth analysis was used to identify groups of enrollees who shared a similar trajectory of change in PCL score in the time period prior to Sandy. We compared enrollees in each trajectory group to assess the impact of Sandy-related PTSD, Sandy exposures, and optimism on 9/11-related PTSD status post-Sandy (2015–16) using bivariate analyses and multivariable log-binomial regression. Sandy-related PTSD was the strongest predictor of subsequent 9/11-related PTSD. Lower optimism and higher Sandy exposure significantly predicted 9/11-related PTSD only in some trajectory groups. Hurricane Sandy may have exacerbated previously resolved symptoms of 9/11-related PTSD. This indicates a need after a disaster to assess and address mental health sequelae from previous traumatic exposures.